2018
DOI: 10.1038/s41598-018-24377-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of strain and shear wave elastography for qualitative and quantitative assessment of breast masses in the same population

Abstract: We investigated addition of strain and shear wave elastography to conventional ultrasonography for the qualitative and quantitative assessment of breast masses; cut-off points were determined for strain ratio, elasticity ratio, and visual score for differentiating between benign and malignant masses. In all, 108 masses from 94 patients were evaluated with strain and shear wave elastography and scored for suspicion of malignancy, visual score, strain ratio, and elasticity ratio. The diagnostic performance betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 27 publications
4
27
0
Order By: Relevance
“…The sensitivity and specificity of sonoelastography are 88.5% and 92.7%, respectively [29]. The distinction between benign and malignant tissues in sonoelastography is important and is still subject of discussion [28]. In general, the sonoelastography technique is performed in two ways: stress elastography (SE) and shear wave elastography (SWE) [30].…”
Section: Tissue Elasticity Imaging (Sonoelastography)mentioning
confidence: 99%
See 3 more Smart Citations
“…The sensitivity and specificity of sonoelastography are 88.5% and 92.7%, respectively [29]. The distinction between benign and malignant tissues in sonoelastography is important and is still subject of discussion [28]. In general, the sonoelastography technique is performed in two ways: stress elastography (SE) and shear wave elastography (SWE) [30].…”
Section: Tissue Elasticity Imaging (Sonoelastography)mentioning
confidence: 99%
“…In general, the sonoelastography technique is performed in two ways: stress elastography (SE) and shear wave elastography (SWE) [30]. Studies have shown that there is no significant difference between SE and SWE ultrasonography, and both have similar sensitivity and specificity when compared with conventional sonography [28].…”
Section: Tissue Elasticity Imaging (Sonoelastography)mentioning
confidence: 99%
See 2 more Smart Citations
“…SWE produces elastographic color maps capable of providing quantitative elasticity measurements in a user-defined region of interest (ROI) at different sites, such as superficial or deep soft tissues. Importantly, in contrast to strain elastography, SWE does not require any operator compression or a mechanical source for the stress generation and, hence, is a more reproducible technique [15]. SWE has been applied to head and neck tissues and, more specifically, to evaluate the elastic properties of the masseter muscle [16,17], cervical muscles [18,19], salivary glands [20] and thyroid [21,22].…”
Section: Introductionmentioning
confidence: 99%